Review of Anopheles Mosquito Species, Abundance, and Distribution in Ethiopia - Fasil Adugna; Melaku Wale; Endalkachew Nibret (Journal of Tropical Medicine)
Background. Malaria is a major mosquito-borne disease in Ethiopia, and it is one of the leading causes of morbidity and mortality. Plasmodium falciparum and P. vivax are the two malaria-causing parasitic species commonly known to cause human malaria in Ethiopia. To better manage and control vectors transmitting malaria parasites, the abundance, distribution, and updated annotated list of Anopheles species present in Ethiopia are very important. Methods. In order to compile a list of the species recorded in Ethiopia, 33 original research articles were collected. This work gives an updated list of Anopheles mosquito species in Ethiopia and their abundance, distribution, and composition. Results. According to this review, 110305 Anopheles mosquitoes were collected and 35 Anopheles species were recorded in different parts of Ethiopia. A. arabiensis was the most abundant when compared to other species, whereas A. maculipalpis and A. wilsonii were the least abundant species. The most abundant Anopheles species was recorded in central and the least abundant, from eastern Ethiopia. The second, third, and fourth abundant species were also collected from southern, northern, and western parts of Ethiopia.